2004
DOI: 10.1073/pnas.0305901101
|View full text |Cite
|
Sign up to set email alerts
|

Glucose sensing and signaling in Saccharomyces cerevisiae through the Rgt2 glucose sensor and casein kinase I

Abstract: The yeast Saccharomyces cerevisiae senses glucose through two transmembrane glucose sensors, Snf3 and Rgt2. Extracellular glucose causes these sensors to generate an intracellular signal that induces expression of HXT genes encoding glucose transporters by inhibiting the function of Rgt1, a transcriptional repressor of HXT genes. We present the following evidence that suggests that the glucose sensors are coupled to the membrane-associated protein kinase casein kinase I (Yck1). (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
286
4
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(297 citation statements)
references
References 43 publications
5
286
4
1
Order By: Relevance
“…5C). High glucose-induced proteasomal degradation of Mth1 is triggered by glucose activation of the Rgt2 sensor (14,16). Western blot analysis showed that glucose-dependent Mth1 degradation occurs in cells expressing the wild type Rgt2 sensor but not the Rgt2 W529Y sensor (Fig.…”
Section: Glucose Starvation Induces Endocytosis and Vacuolar Degradatmentioning
confidence: 99%
“…5C). High glucose-induced proteasomal degradation of Mth1 is triggered by glucose activation of the Rgt2 sensor (14,16). Western blot analysis showed that glucose-dependent Mth1 degradation occurs in cells expressing the wild type Rgt2 sensor but not the Rgt2 W529Y sensor (Fig.…”
Section: Glucose Starvation Induces Endocytosis and Vacuolar Degradatmentioning
confidence: 99%
“…A high degree of similarity between Stp1 and fungal glucose transporters was observed by means of the BLASTX algorithm. Phylogenetic analysis further revealed that Stp1 did not group with the well characterized cellobiose transporters from N. crassa (CTD1 and CTD2), but rather was closely related to some characterized glucose transporter proteins including HGT-1 from N. crassa (24), MstA from Aspergillus niger (25), as well as glucose sensors Rgt2 and Snf3 from S. cerevisiae (26) (Fig. 2).…”
Section: Isolation Of a Mfs Sugar Transporter Capable Of Transport-mentioning
confidence: 99%
“…It has been shown that Yck1/2-dependent Ssy5 prodomain phosphorylation precedes SCF Grr1 -dependent ubiquitylation (Abdel-Sater et al 2011). In other signaling pathways, Yck1/2-catalyzed phosphorylation has been shown to lead to Grr1-dependent polyubiquitylation and subsequent degradation of the modified substrates by the 26S proteasome (Moriya and Johnston 2004;Spielewoy et al 2004). Hence, the SPS sensor coordinates the activity of general signaling components to achieve a highly specific output (Omnus et al 2011) (Figure 11C).…”
Section: Pathway Genesmentioning
confidence: 99%